Sharp Estimates of the Embedding Constants for Besov Spaces bs p,q, 0 < p < 1 - Evans, W. Desmond; Karadzhov, Gyorgi E.; Edmunds, David E. (Revista Matemática Complutense, 2007)
Sharp estimates are obtained for the rates of blow up of the norms of embeddings of Besov spaces bs p,q in Lorentz spaces as the parameters approach critical values. In [8] the case 1 _ p < 1 was investigated. The case 0 < p < 1 of the present paper requires different methods as the pointwise estimates established are different and the interpolation argument used in [8] is no longer available.